Pendampingan Digital Branding dan Marketing Berbasis E-Commerce Bagi Peternak Susu Sapi Perah Desa Wonokerto Wonosalam Jombang - Nisa, Putri Nur Choirun; Dwi Jayanti, Runtut; Al Akhiri, Reza Al Akhiri; Tri Wulandari, Selvina; Irawati, Tatik (Jurnal Ilmiah Pangabdhi, 2024)
Wonokerto Village is one of the villages in Wonosalam Sub-district. The village's leading sectors are agriculture and dairy farmers. In addition, it also has the natural potential to produce corn, sugar cane, bananas, cassava. The village has independent economic businesses, such as UMKM and dairy cattle. In its development, it is still constrained by marketing, especially in the use of technology, namely in digital marketing and  lack of knowledge of e-commerce-based digital branding and marketing strategies. To determine the results of training and mentoring in e-commerce-based digital branding and marketing with qualitative research methods. Data collection  by observation and questionnaire. The results of the training and assistance regarding e-commerce-based digital branding and marketing are in the form of an Instagram social media platform with the account names @susumoow and @sumudewo.